Representasi Kecantikan Perempuan Berhijab pada Akun Instagram Selebgram Hijab (Analisis Wacana Sara Mills) - Dina, Nisa Bela; S, Hapsari Dwiningtyas; Gono, Joyo NS; Rahmiaji, Lintang Ratri (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
The aim of this observation is to explain how beauty is being represented through instragram accounts of veiled selebgram. This observation uses three instragram accounts of Indonesian veiled selebgram which comprises stylish veiled selebgram, syar’i veiled selebgram, and niqab selebgram. This thesis is a qualitative observation by using Sara Mills analysis discourse method to examine the text of instagram account of veiled selebgram and to reveal ideologies within. Beauty myth theory and body disciplining by Naomi Wolf is used to unload the myth that enfolds body. The result of this observation shows that beauty myths are still exist, but in a different kind of strategy. Disciplinary in the form of body discipline is done and showed up through body posture, skin, and make up. In the end, veiled women in this text are remain unchained from beauty myth. Religious norm which is compromised with modernity and commercial cannot remove the existing myth.